The Neglected memory of artist Zhang Daqian in Brazil - Gorgulho Braz, Guilherme (Seminário Pesquisar China Contemporânea, 2021)
Over the nearly five decades since his last solo exhibition in Brazil, the Chinese painter, calligrapher and poet Zhang Daqian (1899-1983) was subjected to an involuntary and gradual process of obliteration in the Brazilian art scene, despite its growing popularity on the international scene of the fine arts. The destruction of his iconic Eight Virtues Garden, a Chinese-style site where he lived in Mogi das Cruzes, is one of the best-finished examples of the process of effacement of the artist's memory in Brazil.Named by painter Xu Beihong (1895-1953) as one of the greatest Chinese painters of the past 500 years, Zhang Daqian has risen in popularity in the art market in recent decades. In 2011 and 2016, the Sichuan painter reached the top of the ranking of the most valued artists in auctions worldwide, ahead of exponents of Western visual arts such as Pablo Picasso and Andy Warhol.During the period in which he lived in Brazil, he exhibited with great repercussion in noble cultural spaces and was revered and praised by prominent names in the Brazilian cultural environment. Despite living in Brazil between 1954 and 1973, only two museums currently have his works.The obliteration in Brazilian memory of his contributions to the exchange between Brazil and China largely reflects the phenomenon of Western misunderstanding about the place of Chinese art and culture in the contemporary world in contrast to the ascending protagonism of China in the economic and geopolitical spheres.